RETRACTED: Application of statistical data analysis algorithms and determination of the most significant diagnostic factors - Rozhkova Alena; Kukartsev Vladislav; Kvesko Mikhail; Glinscaya Anna; Kukartseva Oksana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001